2009
DOI: 10.1242/jeb.023580
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the cellular mechanisms of strong luminal alkalinization in the anterior midgut of larval mosquitoes

Abstract: SummaryHere we critically review two recent hypotheses about the mechanism of strong alkalinization by the anterior midgut of mosquito larvae and our tests of these hypotheses. We present experimental evidence against the major components of transport models proposed in these hypotheses. Measurements of the transapical and transbasal proton electrochemical gradients provide an indication of driving forces faced by and generated by the transport mechanisms of the tissue. These measurements confirmed that basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Similarly, Dow's group concluded that Drosophila H + V-ATPase is located in apical membranes (Day et al, 2008), a conclusion supported by Tripathi and associates who provided direct electrophysiological evidence for V-ATPase-generated fluxes of H + toward the basal membranes (Shanbhag and Tripathi, 2009). Again, new evidence from Onken et al (Onken et al, 2009) shows that the apical region of the cytoplasm in epithelial cells of anterior midgut of mosquitoes has a pH as high as 8, which will lead to a re-evaluation of models of pH regulation in mosquito alimentary canal.…”
Section: Complexity Of Membrane Energization and Energy Utilizationmentioning
confidence: 85%
“…Similarly, Dow's group concluded that Drosophila H + V-ATPase is located in apical membranes (Day et al, 2008), a conclusion supported by Tripathi and associates who provided direct electrophysiological evidence for V-ATPase-generated fluxes of H + toward the basal membranes (Shanbhag and Tripathi, 2009). Again, new evidence from Onken et al (Onken et al, 2009) shows that the apical region of the cytoplasm in epithelial cells of anterior midgut of mosquitoes has a pH as high as 8, which will lead to a re-evaluation of models of pH regulation in mosquito alimentary canal.…”
Section: Complexity Of Membrane Energization and Energy Utilizationmentioning
confidence: 85%
“…Serotonin is also involved in regulation of peripheral tissues in larval A. aegypti, but the role of serotonin in the physiological responses of larval A. aegypti to feeding are less clear than in Rhodnius. Serotonin stimulates acid/base transport of the larval mosquito midgut, and fluid secretion by the Malpighian tubules (Clark and Bradley, 1996;Clark and Bradley, 1997;Clark et al, 1999;Onken et al, 2008;Onken and Moffett, 2009); actions likely to be associated with feeding. However, Clark and Bradley detected no changes in hemolymph serotonin levels of larval A. aegypti in response to feeding status (Clark and Bradley, 1997).…”
Section: Effects Of Paroxetine On Wriggling Locomotionmentioning
confidence: 99%
“…The physiological roles of VHA in insects (Baumann and Walz, 2012;Onken and Moffett, 2009;Wieczorek et al, 2009) and mammals (Brown et al, 2009;Jefferies et al, 2008;Saroussi and Nelson, 2009;Wagner et al, 2004) are periodically reviewed. Similarly, recent comprehensive reviews have discussed the involvement of VHA in H + secretion and NaCl absorption in freshwater crustaceans, fish and amphibians (Evans et al, 2005;Larsen et al, 2014;Perry and Gilmour, 2006).…”
Section: Introductionmentioning
confidence: 99%